2021
DOI: 10.3389/fnmol.2020.608355
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment and Correlation Analysis of Serum miRNAs in Comorbidity Between Arnold-Chiari and Tourette Syndrome Contribute to Clarify Their Molecular Bases

Abstract: Due to its rarity, coupled to a multifactorial and very heterogeneous nature, the molecular etiology of Arnold-Chiari (AC) syndrome remains almost totally unknown. Its relationship with other neuropsychiatric disorders such as Tourette syndrome (TS) is also undetermined. The rare comorbid status between both disorders (ACTS) complicates the framework of diagnosis and negatively affects the patients' quality of life. In this exploratory study, we aimed to identify serum microRNA expression profiles as molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…However, among the four studies, only the Guo et al study was of high quality. Differential expressions of several miRNAs in TS were reported in the studies by Rizzo et al [ 23 ] and Mirabella et al [ 22 ], and both studies were identified as high quality.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…However, among the four studies, only the Guo et al study was of high quality. Differential expressions of several miRNAs in TS were reported in the studies by Rizzo et al [ 23 ] and Mirabella et al [ 22 ], and both studies were identified as high quality.…”
Section: Resultsmentioning
confidence: 93%
“…Rizzo et al [ 23 ] identified downregulated expression of miR-429 by analyzing 52 TS patients and 15 NC patients (Wilcoxon test p = 0.01; t -test p = 0.004). The study by Mirabella et al [ 22 ] compared TS ( n = 6), TS with Arnold-Chiari syndrome (ACTS) ( n = 11) and NC ( n = 8). The results showed that miR-23a-3p was upregulated in TS compared to NC (1.67-fold), miR-130a-3p was downregulated in ACTS or TS compared to NC (−1.56-fold; −1.61-fold), miR-222-3p and miR-451a were upregulated in ACTS compared to NC (1.95-fold; 1.58-fold), and the FDR was <0.05 for each pairwise comparison.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs (miRNAs) have attracted attention as biomarkers for diseases, intercellular communication, and neural development 49 . A clinical study using serum miRNA expression profiles as molecular fingerprints for children with either TS or Arnold–Chiari malformation showed nine differentially expressed miRNAs as potential molecular tools for the diagnosis of TS 50 . These pathophysiological studies have converged to suggest the importance of CSTC circuits and their associated neurotransmitters and other brain regions but have not yet supported a clear, inclusive theory of tic pathophysiology.…”
Section: Pathophysiologymentioning
confidence: 99%